The Effectiveness of Group Guidance Services to Improve Critical Thinking Skills - Handaka, Irvan Handaka; Setyowati, Aprilia Setyowati; Hendarti, Tri; Jaeti, Nur Fadillah (International Journal of Applied Guidance and Counseling, 2022)
Critical thinking skills must be owned by someone to respond and solve problems in life, preliminary study results show the critical thinking skills of students have not developed or are still low in junior high school N 12 Yogyakarta. This research aims to find out the effectiveness of group guidance services to improve students' critical thinking skills. This type of research is experimental research with true experimental design research methods with post-test control group design pre-test models. The results of the study obtained, from the results of tests that have been done in this study are known that t-hitung results amounted to 5.78 and t-tabel amounted to 2,048. This shows that t-hitung (5.78) > t-tabel (2,048), so Ha is accepted and Ho is rejected. Based on this, it can be concluded that, the alternative hypothesis (Ha) which reads effective group guidance services to improve critical thinking skills of class VIII junior high school N 12 Yogyakarta" received the truth with a significant level of 5%. Thus, demonstrating that group guidance services are effective for improving interpersonal communication.